2016
DOI: 10.1038/tp.2016.206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of induced pluripotent stem cells carrying 22q11.2 deletion

Abstract: Given the complexity and heterogeneity of the genomic architecture underlying schizophrenia, molecular analyses of these patients with defined and large effect-size genomic defects could provide valuable clues. We established human-induced pluripotent stem cells from two schizophrenia patients with the 22q11.2 deletion (two cell lines from each subject, total of four cell lines) and three controls (total of four cell lines). Neurosphere size, neural differentiation efficiency, neurite outgrowth, cellular migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 50 publications
9
90
0
Order By: Relevance
“…We also examined reprogrammed neuronal lineage cells from patients with schizophrenia. Neurospheres are composed of freefloating clusters of neural stem or progenitor cells, differentiated from induced pluripotent stem cells (iPSCs) (Maekawa et al, 2015;Toyoshima et al, 2016). iPSCs-derived neurospheres from schizophrenia patients carrying 22q11.2 micro-deletions ( Fig 6D) (Bundo et al, 2014;Maekawa et al, 2015;Toyoshima et al, 2016) showed a significant increase in CBS mRNA compared to those derived from control subjects ( Fig 6E).…”
Section: Frontal Cortex Lymphocytementioning
confidence: 99%
“…We also examined reprogrammed neuronal lineage cells from patients with schizophrenia. Neurospheres are composed of freefloating clusters of neural stem or progenitor cells, differentiated from induced pluripotent stem cells (iPSCs) (Maekawa et al, 2015;Toyoshima et al, 2016). iPSCs-derived neurospheres from schizophrenia patients carrying 22q11.2 micro-deletions ( Fig 6D) (Bundo et al, 2014;Maekawa et al, 2015;Toyoshima et al, 2016) showed a significant increase in CBS mRNA compared to those derived from control subjects ( Fig 6E).…”
Section: Frontal Cortex Lymphocytementioning
confidence: 99%
“…In addition, genes involved in cell cycle, apoptosis and MAPK pathway were affected [38]. Consistent with this finding, another group also observed disruption of the MAPK pathway in 22q11.2 deletion syndrome in mixed neuronal populations [39], though there was differences in miRNA findings between these two studies [39,40]. This discrepancy may have resulted from small sample size, heterogeneous differentiation or the influence of gene variants not within the CNV.…”
Section: Recent Ipsc-based Cellular Models Of Sczmentioning
confidence: 72%
“…Controls that better match the genetic background (sibling or isogenic control) and more homogeneous differentiation could reduce such discrepancies. The disrupted neurogenesis presumably resulting from dysregulation of the MAPK pathway was partially reversed by treating with the p38 inhibitor, SB203580 [39]. …”
Section: Recent Ipsc-based Cellular Models Of Sczmentioning
confidence: 99%
“…MicroRNA interact with mRNA to regulate the translation and degradation of target mRNA . Zhao et al and Toyoshima et al independently studied the iPSC‐differentiated neurons of patients with 22q11.2 microdeletion, which is another most common SCZD‐associated CNV, and detected a lot of differentially expressed miRNA in the patient iPSC‐derived cells. Differentially expressed miRNA are largely proposed to be involved in neurogenesis, axon guidance, and synaptic plasticity .…”
Section: Research Of Sczd Based On Ipsc Modelsmentioning
confidence: 99%
“…In Zhao et al several miRNA that were previously found to be differentially expressed in SCZD and ASD tissues, such as miR‐34, miR‐4449, miR‐146b‐3p, and miR‐23a‐5p, showed significantly increased expression in the patient iPSC‐derived neurons . In Toyoshima et al downregulated expression of miRNA belonging to the miR‐17/92 cluster and miR‐106a/b promoted gliogenic differentiation of iPSC through enhancing the expression of p38α . Recent research has suggested that microRNA are fundamental for neurodevelopmental deficits in SCZD.…”
Section: Research Of Sczd Based On Ipsc Modelsmentioning
confidence: 99%